PENERAPAN TERAPI MUSIK DANGDUT RITME CEPAT TERHADAP PERBEDAAN TINGKAT DEPRESI PADA PASIEN DEPRESI DI RSJD Dr. AMINO GONDHOHUTOMO PROVINSI JAWA TENGAH: IMPLEMENTATION OF MUSIC THERAPY DANGDUT RITME FAST TO DIFFERENT LEVEL DEPRESSION ON PATIENTS DEPRESSION IN RSJD Dr. AMINO GONDHOHUTOMO CENTRAL JAVA PROVINCE - Eka Yuninda Lutfiani; Tuti Anggarawati (JURNAL KEPERAWATAN SISTHANA, 2019)
Depression is one form of psychiatric disorders in nature of feeling (affective or disorder) is characterized by melancholy, lethargy, feeling of no use, and despair. A nursing action that needs to be administered to patients with depression disorder with the provision of music therapy. Music therapy is a therapy that can improve the effects of analgesics, comfort effects that can reduce depression. Musik used with dangdut music fast rhythm. The purpose of this case study illustrates the changes in depression levels before and after the dangdut music therapy performed rapidly in the space Gatot Kaca RSJD Dr. Amino Gondhohutomo. This type of research is descriptive by using case study approach method. Subyek in this case study were two patients with mild to moderate depression, 18 to 20 years og age, and like dangdut music. Analysis was done descriptively and measured using an HRS-D scale assessment. The result of analysis after the music therapy dangdut fast rhythm for 4 times on subjects I and subjects II, showed that the occurrence of decreased depression rate with subjects I score 13 (mild depression) to 6 (normal) and subjects II 16 (moderate depression) to 12 (mild depression). Recommendations for nurse may continue nursing actions to lower dep levels.